The realist case for global reform - Scheuerman, William E. (Cambridge, UK : Polity, 2011)
A reconsideration of the main figures of international political theory. It challenges conventional wisdom to reveal a neglected tradition of Progressive Realism contributing to debates about international policy-making and world government
Includes bibliographical references and index
BSBA
Keywords: International relations; World politics